Finite element simulation of laser transmission thermoplastic welding of circular contour using a moving heat source. (1st January 2013) - Acherjee, Bappa; Kuar, Arunanshu S.; Mitra, Souren; Misra, Dipten
In the present research, a three-dimensional transient numerical model is developed to simulate the laser transmission welding of circular contours. Polycarbonate, a thermoplastic material, is considered as work material for developing and validating the model. The welding simulation is performed, to compute the temperature distribution and shape and size of the molten pool, using the commercial finite element software ANSYS ® . The results numerical analysis is further used for investigating the parametric effect on temperature field and weld bead profile. The results obtained revealthat laser power has a positive effect on all the responses investigated; whereas, welding speed has a negative effect. For constant line energy, higher temperature is obtained at a combination of high power with high welding speed.